Bangladesh's updated Nationally Determined Contributions (NDCs) with quantified measures to reduce Greenhouse Gas (GHG) emissions in rice production - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Bangladesh improved the quantification of scaling plans for low-emission rice production from an estimated percentage of rice area (INDC) to explicitly quantified targets in hectares in their updated NDCs